2011
DOI: 10.1021/ol200372y
|View full text |Cite
|
Sign up to set email alerts
|

Iron-Catalyzed Stereospecific Olefin Synthesis by Direct Coupling of Alcohols and Alkenes with Alcohols

Abstract: An efficient Fe(III)-catalyzed direct coupling of alkenes with alcohols and cross-coupling of alcohols with alcohols to give the corresponding substituted (E)-alkenes stereospecifically is demonstrated. Additionally, this reaction could be scaled up. The kinetic isotope effect (KIE) experiments indicated a typical secondary isotope effect in this process. Although benzylic alcohols were effective substrates, mild conditions, atom efficiency, environmental soundness, and stereospecificity are features that make… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(42 citation statements)
references
References 54 publications
1
40
0
1
Order By: Relevance
“…The majority of known methods include the use of very effective transition metal catalysts, such as complexes of Pd, Cu, Ni, Fe, Ru and Lewis acids based on weak metals (e.g. Bi, In and Ga) [7][8][9][10][11][12][13][14][15][16][17]. However, toxicity of organometallic reagents and their removal to meet the strict specifications of pharmaceutical grade purity is a challenging and demanding process.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of known methods include the use of very effective transition metal catalysts, such as complexes of Pd, Cu, Ni, Fe, Ru and Lewis acids based on weak metals (e.g. Bi, In and Ga) [7][8][9][10][11][12][13][14][15][16][17]. However, toxicity of organometallic reagents and their removal to meet the strict specifications of pharmaceutical grade purity is a challenging and demanding process.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] Almost all of these methods were limited to specific alcohols or alkenes and suffered from low yields and/or the relatively complicated reaction conditions. Muzart et al reported that H 6 P 2 W 18 O 62 catalyzed the direct coupling of 1-indanol with styrene to form 2,3-dihydro-1-styryl-1H-indene in very low yield and selectivity.…”
mentioning
confidence: 99%
“…[8] Very recently, Liu et al reported that FeCl 3 ·6 H 2 O catalyzed the direct coupling of aromatic olefins with benzylic alcohols to give substituted alkenes in the presence of a stoichiometric amount of TsOH. [9] The present method for the direct coupling of benzylic, allylic, and propargylic alcohols with un- activated aromatic and aliphatic alkenes is realized under mild conditions by employing a simple Brøn-A C H T U N G T R E N N U N G sted acid, TfOH, [10] (7.5 mol%) as catalyst, which provides a wide range of polysubstituted olefins in good to excellent yields and high selectivity. Interestingly, when some cyclic alkenes or 3,3-disubstituted branched chain olefins were used to react with benzhydrol, a different 1,2-hydride shift of the carbocation intermediate or a cyclization reaction of the carbocation intermediate with the aromatic ring occurred under our standard conditions, which offers attractive strategies for the construction of tetrasubstituted olefins or indane compounds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2009, Nishimoto et al [30] reported an -alkylation of carbonyl compounds by FeCl 3 -catalyzed addition of enol acetates to alcohols. In 2011, an efficient Fe(III)-catalyzed direct coupling of alkenes with alcohols and cross-coupling of alcohols with alcohols to give the corresponding substituted (E)-alkenes stereospecifically was developed by us [31].…”
Section: Methodsmentioning
confidence: 99%